Early Diagnosis of Nonconvulsive Status Epilepticus Recurrence with Raw EEG of a Bispectral Index Monitor - Aristide Ntahe (Case Reports in Critical Care)
Background. Seizures are frequent in ICU and their diagnosis is challenging, often delayed or missed. Their diagnosis requires a conventional EEG recording. When cEEG is not available, there is no consensus on how patients should be monitored when there is high risk of seizure. This case illustrates how a bispectral index monitor allowed an early diagnosis of an NCSE recurrence. Case Presentation. A NCSE was diagnosed at the admission. cEEG was not available and then a bispectral index (BIS) monitor was placed and processed parameters were monitored as usual. During the first and second day, both conventional and BIS’s EEG showed patterns of burst suppression and the BIS value varied between 25 and 35 while the suppression ratio (SR) varied between 20 and 35. On the third day, while hypnotic drugs were withdrawn progressively, raw EEG of the BIS monitor showed spikes, spikes waves, and polyspikes without significant variation of BIS and SR values. Even if processed parameters stayed between their usual ranges, the typical aspect of the real time EEG raised concern for NCSE recurrence. An unplanned conventional EEG recording was urgently requested, and the diagnosis was confirmed and treated. Conclusion. Primitive and secondary brain injuries can lead to seizures which are often purely electrical. Even though BIS monitors cannot substitute the conventional EEG, processed parameters and raw EEG should be always analysed jointly. In the present case, seizure was suspected only on the aspect of real time EEG which showed spikes, spikes waves, and polyspikes.